Diabetic Nephropathy without Diabetes - López-Revuelta, Katia (J Clin Med, 2015)
Diabetic nephropathy without diabetes (DNND), previously known as idiopathic nodular glomerulosclerosis, is an uncommon entity and thus rarely suspected; diagnosis is histological once diabetes is discarded. In this study we describe two new cases of DNND and review the literature. We analyzed all the individualized data of previous publications except one series of attached data. DNND appears to be favored by recognized cardiovascular risk factors. However, in contrast with diabetes, apparently no factor alone has been demonstrated to be sufficient to develop DNND. Other factors not considered as genetic and environmental factors could play a role or interact. The most plausible hypothesis for the occurrence of DNND would be a special form of atherosclerotic or metabolic glomerulopathy than can occur with or without diabetes. The clinical spectrum of cardiovascular risk factors and histological findings support this theory, with hypertension as one of the characteristic clinical features.